Explaining Northern Ireland? The limitations of the ethnic conflict model - Cillian McGrattan (National Identities, 2010)
This article claims that while the concept of ethno-nationalism may be taken as shorthand for describing what appear to be the dominant features of certain political conflicts, it possesses little explanatory value – instead obscuring and confusing more than it reveals. Using the Northern Ireland case as an illustrative example, it is argued that the reluctance to problematise or contextualise ethnic claims means that ethnic conflict theorists may effectively contribute to the reproduction of dominant narratives. The article explicitly rejects the notion that a single framework should replace the ethno-national model. Instead, it highlights the importance of focusing issues of timing and historical sequencing, source criticism and empirical evidence, as well as the significance of marginal narratives and experiences.